Penerapan Metode Multiplicative Decomposition (Seasonal) Untuk Peramalan Produksi Al-Qur’an - Fayaqun, Reza; Sumarna, Dani Leonidas; Sulistiyaningsih, Febriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Production planning is crucial for companies, especially for best-selling products. The B5-sized Qur'an is a best-selling product, especially around Eid al-Fitr and major Muslim holidays. Fluctuations in demand, which tend to fluctuate, force Qur'an-producing companies to plan production in a measurable manner. This is absolutely essential to ensure that production output can meet future demand. A suitable method for forecasting production with such a demand pattern is Multiplicative Decomposition (Seasonal). This method is often used not only to generate forecasts but also to generate information regarding the components of time series and the appearance of various factors, such as trends, cycles, seasonality, and irregularities in the observed results. The results of the forecasting calculations using the Multiplicative Decomposition method show that the MAD value is 240.84, MSE 89,811.47 and MAPE 0.1 or 10% where the MAPE error is relatively small, below 20%, so it is hoped that the Multiplicative Decomposition method can be used as a method for forecasting the production of B5-sized Al-Qur'ans in the future period.